Radiation Exposure During Uterine Fibroid Embolization (UFE): A Confounder-Controlled Comparison Between a State-of-the-Art Angiography Unit and a Conventional Angiography unit - Sommer, Christof-Matthias; Voigt, Wieland; Klapp Oliger, Michel; Schlett, Christopher L; Erpenbach, Stefan; Thomas, Katrina; Hatopp, Andreas; Kurz, Patrick; Richter, Goetz M (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Purpose To compare radiation exposure of a state-of-the-art and a conventional angiography unit in patients undergoing uterine fibroid embolization (UFE).Materials and Methods Between January 2009 and December 2016, 286 patients underwent UFE in our Interdisciplinary Fibroid Center. The inclusion criteria for this retrospective analysis were first-time transarterial embolization for symptomatic fibroids, bilateral embolization, procedures applying a state-of-the-art (Group 1) or a conventional angiography unit (Group 2), and bilateral technical success with an adequate embolization endpoint after the injection of microspheres. Study endpoints included radiation exposure, major complications, morphological success (MRI), and clinical success (questionnaire on quality-of-life). Propensity score matching controlled for confounders.Results The inclusion criteria were met by 58 (Group 1) and 177 (Group 2) patients. After propensity score matching, there was no significant difference between Group 1 (n = 46) and Group 2 (n = 92) regarding age, body-mass index, volume of the dominant fibroid and the uterus, fluoroscopy time, and amount of embolic agent (p ≥ 0.10 each). The dose-area product was significantly lower in Group 1 than in Group 2 (1159.0 cGycm2 vs. 3123.5 cGycm2; p < 0.001), while major complication rates (both groups 0 %) and dominant fibroid devascularization (both groups 100 %) were equal (p > 0.99). There were no significant differences between both groups regarding shrinkage of the dominant fibroid and the uterus and no relevant differences regarding patient-reported quality-of-life.Conclusion A state-of-the-art angiography unit has the potential to reduce radiation exposure in patients undergoing UFE without increasing the risk of major complications and with comparably high morphological and clinical success.Key Points Citation Format
Keywords: radiation exposure; dose reduction; propensity score matching; quality-of-life; uterine fibroid embolization